Relict populations of Diaphanosoma (Cladocera: Ctenopoda) in the Chadian Sahara, with the description of a new species - Guo, Fei-Fei; Dumont, Henri J. (Zootaxa, 2014)
We record two species of Diaphanosoma from Ounianga and Tibesti in Northern Chad, the first ctenopods to be found in the Sahara desert. One species, from a freshwater guelta on the south flanks of the Tibesti (D. excisum) is tropical; the second species, found in a freshwater lake in a largely saline environment (the Ounianga plateau) is new to science (D. bopingi sp.nov.) and is here described, with special attention to some previously unnoticed structures on the postabdomen. Its relatives are northern species that may transgress into the tropics but largely live outside of them. They are also more salt-tolerant than the tropical D. excisum. The latter is considered a relict of Megachad times, while the new species is considered a relict of more humid but also cooler times in the desert.